Relationship Between Social Media use with Adolescents Stress Levels in Bentian Besar 1 Senior High School - Prasetiawan Prasetiawan (Rifa'Institute, 2023)
Introduction: social media is a medium on the internet that allows users to represent themselves and interact, collaborate, share, communicate with other users, and form virtual social bonds. Playing too much social media can cause stress in teenagers. Stress is a condition of a person experiencing an imbalance between what is desired and reality. Objective: To determine the relationship between social media use and stress levels in Bentian Besar 1 Senior High School adolescents. Methods: The research design in this study was descriptive correlation using a cross-sectional approach. The study was conducted in January 2022. Determination of the sample Stratified Random sampling, the research sample amounted to 132 respondents. The statistical test used is Chi-Square if it is obtained t arithmetic (p-value) <0.05, then the hypothesis Ha is accepted and Ho is rejected. Results and Discussion: The use of social media in the rare category (48.5%), stress levels in the moderate category (41.7%). There is a relationship between the use of social media with stress levels in adolescents (p-value = 0.00). Conclusion: There is a relationship between the use of social media with the level of Adolescents at Bentian Besar 1 Senior High School.